Bicuculline restores frequency-dependent hippocampal I/E ratio and circuit function in PGC-1ɑ null mice. (November 2022) - Bhattacharya, Dwipayan; Bartley, Aundrea F.; Li, Qin; Dobrunz, Lynn E.
Abstract: Altered inhibition/excitation (I/E) balance contributes to various brain disorders. Dysfunctional GABAergic interneurons enhance or reduce inhibition, resulting in I/E imbalances. Differences in short-term plasticity between excitation and inhibition cause frequency-dependence of the I/E ratio, which can be altered by GABAergic dysfunction. However, it is unknown whether I/E imbalances can be rescued pharmacologically using a single dose when the imbalance magnitude is frequency-dependent. Loss of PGC-1α (peroxisome proliferator activated receptor γ coactivator 1α) causes transcriptional dysregulation in hippocampal GABAergic interneurons. PGC-1α -/- slices have enhanced baseline inhibition onto CA1 pyramidal cells, causing increased I/E ratio and impaired circuit function. High frequency stimulation reduces the I/E ratio and recovers circuit function in PGC-1α -/- slices. Here we tested if using a low dose of bicuculline that can restore baseline I/E ratio can also rescue the frequency-dependent I/E imbalances in these mice. Remarkably, bicuculline did not reduce the I/E ratio below that of wild type during high frequency stimulation. Interestingly, bicuculline enhanced the paired-pulse ratio (PPR) of disynaptic inhibition without changing the monosynaptic inhibition PPR, suggesting that bicuculline modifies interneuron recruitment and not GABA release. Bicuculline improved CA1 output in PGC-1α -/- slices, enhancing EPSP-spike coupling to wild type levels at high and low frequencies. Our results show that it is possible to rescue frequency-dependent I/E imbalances in an animal model of transcriptional dysregulation with a single treatment. Highlights: Loss of PGC-1a causes a frequency-dependent increase in I/E ratio in hippocampus. A low dose of bicuculline restores the I/E ratio in PGC-1α −/− slices. Bicuculline normalizes the I/E ratio at both short and long paired-pulse intervals. This is through an effect on the paired-pulse ratio of disynaptic inhibition. Restoration of CA1 circuit function in PGC-1α −/− slices occurs with bicuculline.